UNP Chemistry Students’ Perception of Using References Written in English - Diah Fauzanah; Sitti Fatimah (Journal of English Language Teaching, 2019)
Chemical Department has used references including some textbooks written in English as the medium of instruction in teaching and learning process. Some students find difficulties to understand textbooks written in English because of some reasons which brings out different perceptions about the use of references in English to the student. This research aims to find out Chemistry students’ perception of using refernces written in English. This research is a quantitative research which used descriptive method. There were 56 Chemistry students as the sample of this research which choosen by using cluster sampling technique. The istrument used in this research is the questionnaire about students’ perception which based on three perception indicator; absorption, understanding and evaluation. The findings shows that the students have positive perception toward the use of refernces written in English viewed from absorption and evaluation indicator, and negative perception viewed from understanding indicator.